Frequency of Factors Leading to the Development of Urolithiasis at SIUT, Karachi - Abbas, Syeda Zoha; Shehzad Shah, Syed Arslan; Qureshi, Harris Hassan; Zehra, Farzeen; Maher, Naveed; Hussain, Manzoor; Hassan Rizvi, Syed Adibul (Biological and Clinical Sciences Research Journal, 2025)
Urolithiasis is a common urological condition worldwide and a significant cause of morbidity, especially in regions with hot climates and dietary variations such as Pakistan. Understanding the contributing factors is essential for prevention and management. Objective: To determine the frequency of factors leading to the development of urolithiasis at SIUT, Karachi. Methodology: We conducted this study on 385 participants aged 20-70 years presenting with acute renal colic and a confirmed ultrasonographic diagnosis of urolithiasis. Data on predefined demographic and risk factors were collected. Results: The mean age of the 385 participants was 49.49 ± 14.09 years. A majority were male (62.3%), and the most prevalent modifiable risk factor was low water intake (65.7%), which was followed by obesity (51.9%) and aerated beverage consumption (56.4%). Comorbid risk conditions were highly prevalent, including hypertension (37.9%), anemia (48.8%), and diabetes mellitus (28.3%). A strong family history of urolithiasis was reported in 47.5% of the cohort. Other significant factors included an age greater than 50 years (53.8%) and smoking (24.9%). Conclusion: The risk factors leading to the development of urolithiasis were the high frequency of male sex and increasing age, with modifiable risks such as low water intake and comorbid metabolic conditions.